2006
DOI: 10.1111/j.1747-0803.2006.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Arch Thrombosis in a Neonate With Heterozygous Carrier Status of Factor V Leiden Mutation

Abstract: Neonatal spontaneous aortic arch thrombosis without an anatomical correlate is an extremely rare disorder of unknown etiology. A 1-day-old newborn was admitted with suspicion of the coarctation of the aorta. Angiography revealed congenital occluding thrombosis of the ascending aorta and the aortic arch. Surgery was considered impossible because of concomitant thrombosis of the inferior vena cava and the right renal vein. Thrombolysis with streptokinase and tissue plasminogen activator was attempted unsuccessfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…Metsvaht et al stressed on the striking prevalence of male gender among patients with spontaneous neonatal aortic arch thrombosis that might suggest the role of sex-linked inherited factors in the penetrance of disease, as autosomal dominant inheritance has been established for the FVL mutation [33]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metsvaht et al stressed on the striking prevalence of male gender among patients with spontaneous neonatal aortic arch thrombosis that might suggest the role of sex-linked inherited factors in the penetrance of disease, as autosomal dominant inheritance has been established for the FVL mutation [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Increased rates of still birth, miscarriage, abruption of placenta, placental infarction, intrauterine fetal growth retardation, prematurity, and intrauterine fetal thrombosis were explained to the parents [11, 16, 5961]. …”
Section: Discussionmentioning
confidence: 99%
“…Cases of heterozygous FVL mutation causing arterial disease are rare and have been described mostly in neonates [10-12]. Other cases of aortic arch and peripheral arterial thrombosis have also been reported in adults [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…When we screened the literature, we found 10 cases where AC or IA was considered initially, but a diagnosis of aortic thrombosis was made subsequently (Table 1) (3)(4)(5)(6)(7)(8)(9)(10)(11). In 9 of these 10 patients, the symptoms started in the first 48 hours of life as in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Metsvaht et al (3) reported that they found congenital obstructive thrombosis in the arcus aorta and ascending aorta on angiography in a one-day old patient who was investigated because of suspicious AC in 2006. Findings of cardiopulmonary failure started in the first 48 hours of life as in our patient, bilateral femoral pulses were inpalpable, renal functions tests and transaminase levels were increased and PEG2 infusion was initiated considering AC or IA with ECHO findings.…”
Section: Discussionmentioning
confidence: 99%